Local media and political practices: Notes for addressing mediatization - Rusconi, Carlos (2021)
The major issue underpinning this research paper is how to address the fundamental question concerning media, that is, to what extent and how media permeate contemporary society and culture. In this context, we aim to put forward a methodological proposal on how to account for mediatization. This concept emphasizes the networks connecting media actors with actors in the most diverse social spheres. These networks are important given that they comprise the arena in which meaning is constructed. Although in recent years this concept has been very helpful in order to understand theoretically the key role played by media in the process of social and cultural change, there are not many methodological proposals based on it, and some of the existent ones are defined from deterministic macro-approaches, indifferent to the developments of the constructivist paradigm. On the basis of a methodological qualitative design that seeks to reconstruct and analyze the interactions linking media actors (mainly journalists) with politicians and neighborhood associations, we examine the resulting networks and their different levels of communication. Therefore, the paper addresses four main topics: first, a theoretical overview of the category of mediatization. Second, the presentation of an interactional approach grounded in some important categories of the constructivist paradigm. Third, a proposal based on qualitative research covering the mediatization of political practices in a middle-sized city in Argentina. Finally, an epistemological question regarding the major level of media interaction, i.e., the mediatization of the public sphere.